Analysis of Treatment of Fixed Assets Based on Government Accounting Standard Statement No.07 at the Likupang Timur District Office North Minahasa District - MOKOGINTA, Lidya Teresa; WARONGAN, Jessy D.L; PUSUNG, Rudy (Journal of Governance, Taxation and Auditing, 2024)
Accounting treatment related to fixed assets includes determining the acquisition price or value of fixed assets, depreciation of fixed assets, and write-offs. The main objective of acquiring fixed assets is to improve community welfare through improving government services. This research aims to determine whether the accounting treatment for fixed assets at the East Likupang District Office is according to the Government Accounting Standards Statement Number 07 concerning Fixed Asset Accounting Based on Government Regulation of the Republic of Indonesia Number 71 of 2010 concerning Government Accounting Standards. This analysis method is descriptive qualitative. The research results show that the East Likupang District Office still needs to fully implement the Government Accounting Standards Statement No. 07 Government Regulation Number 71 of 2010. The information on depreciation of fixed assets still needs to be completed in CALK because the accumulated depreciation is the only value. There is no disclosure of information regarding depreciation, so it is yet to be available by PSAP No. 07.